2017
DOI: 10.1111/acer.13538
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive Personality Traits Mediate the Relationship Between Adult Attention‐Deficit/Hyperactivity Symptoms and Alcohol Dependence Severity

Abstract: These results highlight the importance of looking at cohorts of ADHD symptoms and facets of impulsivity to assess the risk of developing AUD. They also suggest potential avenues for intervention strategies in individuals with preexisting adult ADHD symptoms who are seeking treatment for AUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 50 publications
4
26
0
Order By: Relevance
“…Negative urgency has also been linked to the higher prevalence of comorbid AUD in adults with attention-deficit/hyperactivity disorder (ADHD; Daurio et al, 2018). In a study of 794 adult subjects, different components of impulsivity were tested to understand the relationship between ADHD symptoms and the severity of alcohol dependence.…”
Section: Negative Urgency and Addiction: Tobacco Alcohol Cocaine Pmentioning
confidence: 99%
“…Negative urgency has also been linked to the higher prevalence of comorbid AUD in adults with attention-deficit/hyperactivity disorder (ADHD; Daurio et al, 2018). In a study of 794 adult subjects, different components of impulsivity were tested to understand the relationship between ADHD symptoms and the severity of alcohol dependence.…”
Section: Negative Urgency and Addiction: Tobacco Alcohol Cocaine Pmentioning
confidence: 99%
“…A recent large study reported that symptoms of hyperactivity/restlessness and problems with self-concept increased the odds of having a diagnosis of ADHD and that impulsivity mediated the relationship between adult ADHD symptoms and alcohol dependence severity [40]. A Dutch study showed higher levels of motor and cognitive impulsivity in ADHD patients with comorbid cocaine dependence compared to ADHD patients without cocaine dependence and controls [41].…”
Section: Prevalence and Symptom Severitymentioning
confidence: 99%
“…It is worth to notice that children with ADHD are signi icantly more likely to develop substance use disorders than children without ADHD [8][9][10]. Indeed, previous studies have already shown that ADHD is a risk factor for the onset and the development of addiction to substances, like alcohol and drugs [11][12][13].…”
Section: Introductionmentioning
confidence: 99%